Exonic splicing code and protein binding sites for calcium - Pengelly, Reuben J; Bakhtiar, Dara; Borovská, Ivana; Královičová, Jana; Vořechovský, Igor (Nucleic acids research, 2022)
Abstract Auxilliary splicing sequences in exons, known as enhancers (ESEs) and silencers (ESSs), have been subject to strong selection pressures at the RNA and protein level. The protein component of this splicing code is substantial, recently estimated at ∼50% of the total information within ESEs, but remains poorly understood. The ESE/ESS profiles were previously associated with the Irving-Williams (I-W) stability series for divalent metals, suggesting that the ESE/ESS evolution was shaped by metal binding sites. Here, we have examined splicing activities of exonic sequences that encode protein binding sites for Ca2+, a weak binder in the I-W affinity order. We found that predicted exon inclusion levels for the EF-hand motifs and for Ca2+-binding residues in nonEF-hand proteins were higher than for average exons. For canonical EF-hands, the increase was centred on the EF-hand chelation loop and, in particular, on Ca2+-coordinating residues, with a 1>12>3∼5>9 hierarchy in the 12-codon loop consensus and usage bias at codons 1 and 12. The same hierarchy but a lower increase was observed for noncanonical EF-hands, except for S100 proteins. EF-hand loops preferentially accumulated exon splits in two clusters, one located in their N-terminal halves and the other around codon 12. Using splicing assays and published crosslinking and immunoprecipitation data, we identify candidate trans-acting factors that preferentially bind conserved GA-rich motifs encoding negatively charged amino acids in the loops. Together, these data provide evidence for the high capacity of codons for Ca2+-coordinating residues to be retained in mature transcripts, facilitating their exon-level expansion during eukaryotic evolution.